The relationship between esg and corporate financial performance during the covid-19 crisis - Wong, Winnie Yee Ching (2023)
This study aimed to investigate the relationship between ESG factors and financial performance of companies during the COVID-19 pandemic. The results of the study did not provide sufficient evidence to support the hypothesis that there is a positive relationship between ESG factors and financial performance. The statistical analysis showed that the correlations observed between ESG factors and financial performance were not statistically significant at the 0.05 level, indicating that the sample of companies studied does not demonstrate a clear and consistent relationship between these variables. The regression analysis also revealed that the ESG score was not a statistically significant predictor of ROA during any of the years (2019- 2022) analysed. These findings suggest that ESG scores may not be a significant predictor of financial performance for the given years, and the model's accuracy in predicting financial performance varied across years. The study's results provide insights into the limitations of the relationship between ESG and financial performance, which policymakers and investors must take into consideration. Further inquiry is required to gain a deeper understanding of the underlying causes for these disparities.